(untitled) (Conference on English Language Teaching, 2023)
The focus of this research is (1) how are the pedagogical competencies that lecturers must have in the Industrial Revolution 4.0 to 5.0 era to shape student character in learning English (2) how lecturers instill character education in the Industrial Revolution 4.0 to 5.0 era of learning English (3) how are the efforts of lecturers in the era of the industrial revolution 4.0 towards 5.0 to overcome obstacles to instilling character education in learning English. The population of this research was five English lecturers as a sample for Syariah Faculty at the state of Islamic University of Fatmawati Sukarno Bengkulu and this research also used the totality sampling. The Collecting data of this research used the trianggulation namely, observation, Interview and documentation. Analysis of the data based on Miles and Huburman’s theory were reduction, display and conclusion-veryfication. The results of this research showed that, (1) The pedagogic competencies that must be possessed by lecturers in the era of the industrial revolution 4.0 to 5.0 to shape student character in learning English, namely lecturers are able to integrate character education values when preparing teaching plans and syllabus based on Internet Things, preparing teaching materials based on virtual/augmented reality, applying Artificial Intelligence-based learning. (2) lecturers must be able to instill character education in learning English in the era of the industrial revolution 4.0 towards 5.0 by incorporating religious character values, morals, responsibility and discipline in the learning process and implementing habits on campus that support the formation of 4C-based characters (creativity), critical thinking, communication and collaboration) in the era of society 4.0 towards 5.0. (3) Efforts to make agreements between lecturers, students, and student families to provide a deterrent effect to students who violate the rules during learning takes place